Principles of superconducting quantum computers - Stancil, Daniel D.; Byrd, Gregory T. (Hoboken: John Wiley & Sons, 2022)
"Digital systems that are most familiar are based on binary digits, or "bits." Each bit can take on either the value "1" or "0", and any arbitrary data can be represented by such a binary representation. In addition, any arbitrary logical operation can be implemented using bits. The text refers to these familiar systems as "classical" systems, since they are governed by the everyday laws of classical physics. Quantum computing is different from classical computing in a number of significant ways, as discussed in 'Principles of superconducting quantum computers'"--
Includes bibliographical references and index.
Keywords: Quantum computers; Superconducting quantum interference devices